Laser Fabrication of Gold–sp-Carbon Films - Stella Kavokina; Anton Osipov; Vlad Samyshkin; Andrey Abramov; Natalia Rozhkova; Vitali Kononenko; Vitali Konov; Alexey Kucherik (Condensed Matter, 2023)
We develop a method for the laser synthesis and deposition of carbon–gold films formed by a net of linear sp-carbon chains and stabilized by gold nanoparticles. The originality of the method is in the simultaneous production of carbon chains and gold nanoparticles due to the laser fragmentation of the amorphous carbon and hydrogen tetrachloroaurate (III) or chloroauric acid. We study how surface resistivity alters the effect of the obtained films via the illumination in the visible spectral range.